Observations and Modeling of Increased Nitric Oxide in the Antarctic Polar Middle Atmosphere Associated With Geomagnetic Storm‐Driven Energetic Electron Precipitation. Issue 7 (28th July 2018) - Newnham, D. A.; Clilverd, M. A.; Rodger, C. J.; Hendrickx, K.; Megner, L.; Kavanagh, A. J.; Seppälä, A.; Verronen, P. T.; Andersson, M. E.; Marsh, D. R.; Kovács, T.; Feng, W.; et al.
Abstract: Nitric oxide (NO) produced in the polar middle and upper atmosphere by energetic particle precipitation depletes ozone in the mesosphere and, following vertical transport in the winter polar vortex, in the stratosphere. Medium‐energy electron (MEE) ionization by 30–1, 000 keV electrons during geomagnetic storms may have a significant role in mesospheric NO production. However, questions remain about the relative importance of direct NO production by MEE at altitudes 60–90 km versus indirect NO originating from auroral ionization above 90 km. We investigate potential drivers of NO variability in the southern‐hemisphere mesosphere and lower thermosphere during 2013–2014. Contrasting geomagnetic activity occurred during the two austral winters, with more numerous moderate storms in the 2013 winter. Ground‐based millimeter‐wave observations of NO from Halley, Antarctica, are compared with measurements by the Solar Occultation For Ice Experiment (SOFIE) spaceborne spectrometer. NO partial columns over the altitude range 65–140 km from the two observational data sets show large day‐to‐day variability and significant disagreement, with Halley values on average 49% higher than the corresponding SOFIE data. SOFIE NO number densities, zonally averaged over geomagnetic latitudes −59° to −65°, are up to 3 × 10 8 /cm 3 higher in the winter of 2013 compared to 2014. Comparisons with a new version of the Whole Atmosphere Community Climate Model, which includes detailed D ‐region ion chemistry (WACCM‐SIC) and MEE ionization rates, show that the model underestimates NO in the winter lower mesosphere whereas thermospheric abundances are too high. This indicates the need to further improve and verify WACCM‐SIC with respect to MEE ionization, thermospheric NO chemistry, and vertical transport. Key Points: NO partial columns over altitudes 65–140 km measured at Halley, Antarctica, are on average 49% higher than SOFIE observations NO number density in the Antarctic mesosphere and lower thermosphere is up to 3 × 10 8 /cm 3 higher in the 2013 winter than the 2014 winter Higher mesospheric NO abundance in the 2013 winter is partially explained by increased NO production due to medium‐energy electrons